Does Working Capital Management Impact Profitability? A Study on ASEAN-5 Food and Beverage Companies - Rahmadani, Salsabila Gading; Pangestuti, Irene Rini Demi (Universitas Airlangga, 2024)
Objective: This study aims to examine the impact of working capital management on profitability of go-public ASEAN-5 food and beverage companies. Design/Methods/Approach: This study employs multiple linear regression analysis on secondary financial data of go-public ASEAN-5 food and beverage companies from 2017-2022. The sample for the research is deliberately chosen through purposive sampling technique. Findings: The results indicate that the cash conversion cycle (CCC), receivable conversion period (RCP), and accounts payable period (APP) have a significant negative impact on profitability, proxied by return on assets (ROA), while the inventory conversion period (ICP) has a positive effect on profitability. Originality/Value: This study uniquely explores the food and beverage sector in the ASEAN-5 region with adding the dimension of crisis, COVID-19 pandemic. Practical/Policy implication: Based on the results, food and beverage sector managers should be more careful in making investment decisions regarding inventory, especially during a crisis. Also, maintaining good trade relations with suppliers through timely debt payment would be better.